National values in Zhuban Moldagaliev's poetry - Malikova, А.Ә.; Omar , Т.Қ.; Baigutova, Д.Н. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The scientific article is devoted to the works of the outstanding poet of Kazakh poetry Zhuban Moldagaliev from 1960 to 1990 and reflects national values in them. On the basis of convincing arguments, the character, mentality and spiritual characteristics inherent in our people are considered, that is, the foundations of national values revealed through the tropes and expressive means of language. The point is that the poet's poetry is divided into thematic and genre forms, such as political and social lyrics, philosophical lyrics, civic lyrics, nature and love lyrics, and sometimes even intertwines with each other and is reflected in the same work. The study also highlights that Moldagaliyev’s poetry from 1960 to 1990 became richer in terms of linguistic expression and artistic style, while his ideas grew more profound. Works by Zhuban Moldagaliyev as one can clearly observe the manifestation of national values such as patriotism, respect for the homeland and native land, glorification of ancestral customs and traditions, strong familial bonds and brotherhood, honesty, hospitality, reverence for parents, women, younger sisters, and elders. Throughout the article, the poet’s civic identity, his unique sense of self (“Men”), and the character of his lyrical persona are clearly revealed.